Trait Emotional Intelligence Moderates the Impact of Failure Feedback: Out-Group Derogation in Fiji. Issue 7 (September 2020) - Johnson, James; Lakhan, Ravinesh; Lecci, Len; Dovidio, John F.; Schellhaas, Fabian M. H.
Two studies investigated the effect of failure feedback, relative to success or no feedback, on the intergroup responses of Fijians of Indian descent (Indo-Fijians, Study 1) and Indigenous Fijians (I-Taukei, Study 2), groups that have a history of intergroup tension, on job suitability ratings of applicants from the negative out-group and from a "neutral" out-group (Asians). For applicants from negative out-groups specifically, compared to participants in the success and no feedback conditions, participants in the failure condition who were low in trait emotional intelligence (TEI) gave poorer negative out-group member suitability ratings. As predicted, TEI moderated the effect of feedback on ratings of the negative out-group member, with participants higher in TEI displaying less negative responding as a function of failure. The moderating impact of TEI on feedback did not occur for candidates from the neutral out-group.